Checklist of Dryinidae (Hymenoptera) from Shaanxi Province, China, with descriptions of two new species - Xu, Zaifu; Olmi, Massimo; Guglielmino, Adalgisa; Chen, Huayan (Zootaxa, 2012)
A checklist of Dryinidae from Shaanxi Province, China, is presented. Two new species, Anteon ningshanense Xu, Olmi,Guglielmino & Chen, sp. nov. and Anteon semirugosum Xu, Olmi, Guglielmino & Chen, sp. nov. are described from theNingshan County, Guanghuojie Town. Five subfamilies, seven genera and 36 species are listed in Shaanxi Province, in-cluding twenty-eight new species records. Of the 36 species now known from Shaanxi, twenty seven species are of Ori-ental origin, six Palaearctic and three are known only from Shaanxi, confirming that the province is a transitional area of Oriental and Palaearctic species.